2007
DOI: 10.1016/j.bbi.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Inducing a mode of NK-resistance to suppression by stress and surgery: A potential approach based on low dose of poly I–C to reduce postoperative cancer metastasis

Abstract: Perioperative suppression of NK activity has been suggested to compromise host resistance to tumor progression. Here we sought to develop a clinically applicable pre-operative regimen to prevent immunosuppression and promotion of metastasis by stress or surgery. The synthetic ds-RNA, poly I-C, was used in vivo in F344 rats, based on its alleged in vitro ability to protect immunocytes from suppression by cAMP elevating agents. Different regimens of poly I-C were studied in controls and in rats subjected to a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…We recently reported that MP-NK cells are uniquely potent and are the only known NK cell population that can effectively kill the syngeneic MADB106 tumor cells 15,26,39 which were used here in both the in vivo studies and in assessing ex vivo MP-NKCA. Therefore, alterations in MP-NK activity against MADB106 may predict alterations in host susceptibility to metastasis of the MADB106 tumor and potentially other autologous tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that MP-NK cells are uniquely potent and are the only known NK cell population that can effectively kill the syngeneic MADB106 tumor cells 15,26,39 which were used here in both the in vivo studies and in assessing ex vivo MP-NKCA. Therefore, alterations in MP-NK activity against MADB106 may predict alterations in host susceptibility to metastasis of the MADB106 tumor and potentially other autologous tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated administration of low-dose polyi:c in a rat model of lung metastasis of mammary adenocarcinoma protected marginating pulmonary NK cells from suppression by surgery. 46,47 A previous study showed that polyi:c was able to inhibit the growth of breast cancer in a mouse model, but preclinical and clinical studies of the antitumor efficacy of polyi:c have been limited by its high toxicity. 48 Urinary tract tumors.…”
Section: Rig-i and Mda-5mentioning
confidence: 99%
“…Intravenous injection of the b-galactoside-specific lectin ML I or its B chain isolated from mistletoe extracts into rabbits resulted in a dose-dependent increase of NK cell cytotoxicity and increased numbers of LGL [105]. Based on these studies, mistletoe preparations were standardized for optimal ML I doses Braedel-Ruoff sia, to which postoperative immunosuppression in experimental models is partly ascribed [134], various therapies are actually tested to prevent suppression of NK cell activity after cancer surgery, such as IL-2 [135], IFN-a [136], polyadenylicpolyuridylic acid [137], cimetidine [67,138], and the Japanese traditional herbal medicine, Hochu-ekki-to (TJ-41) [139], and also the TLR ligand poly-IC is under discussion [140]. In this context, mistletoe therapy is particularly interesting: Intravenous infusion of mistletoe preparations are able to enhance NK cell function [64] and to reduce surgical suppression of NK cell activity in cancer patients [83].…”
Section: Perioperative Mistletoe Infusionmentioning
confidence: 99%